2013
DOI: 10.1177/1363461513498618
|View full text |Cite
|
Sign up to set email alerts
|

At the crossroads of anthropology and epidemiology: Current research in cultural psychiatry in the UK

Abstract: Cultural psychiatry research in the UK comprises a broad range of diverse methodologies, academic disciplines, and subject areas. Methodologies range from epidemiological to anthropological/ethnographic to health services research; mixed methods research is becoming increasingly popular, as are public health and health promotional topics. After briefly outlining the history of cultural psychiatry in the UK we will discuss contemporary research. Prominent themes include: the epidemiology of schizophrenia among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…Total GHQ-20 scores were lower in the Uygur and Kazak minorities than in the majority Han ethnic group, possibly due to beliefs and religious activities that can lower the risk of mental health problems [ 47 ] and often give people hope and support when they are sick or in trouble [ 48 ]. Religious beliefs have also been shown to influence behavior and health in both simple and complex ways [ 49 ], and have been shown to have protective effects against depression and psychosis [ 18 , 50 ]. Additionally, greater religiousness has been shown to be mildly associated with fewer depression symptoms [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total GHQ-20 scores were lower in the Uygur and Kazak minorities than in the majority Han ethnic group, possibly due to beliefs and religious activities that can lower the risk of mental health problems [ 47 ] and often give people hope and support when they are sick or in trouble [ 48 ]. Religious beliefs have also been shown to influence behavior and health in both simple and complex ways [ 49 ], and have been shown to have protective effects against depression and psychosis [ 18 , 50 ]. Additionally, greater religiousness has been shown to be mildly associated with fewer depression symptoms [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, British of African and/or Caribbean descent are more likely to suffer mental health problems compared to their white British counterparts [ 17 ]. Another study found that the Dutch tend to have better mental health than other ethnic groups, which can be partially explained by less stressful working conditions as well as religious beliefs [ 18 , 19 ], which have been shown to have important implications for the promotion of public mental health [ 18 ]. Previous studies have also shown that harsh psychosocial working conditions associated with certain occupational groups can lead to a variety of diseases [ 19 ] including mental health disorders [ 20 , 21 ] and cardiovascular disease [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Jobanaputra and Furnham (2005) found, in a qualitative study, that older and younger Indian immigrants in the United Kingdom were more likely to endorse beliefs about health in relation to supernatural factors than White British. Studies have also found that, when comparing biological and supernatural causes of mental health problems, White British groups mentioned biological causes more frequently than other non-White groups, who endorsed supernatural causes more frequently (Dein & Bhui, 2013).…”
Section: Culture and Causal Explanations Of Mental Healthmentioning
confidence: 99%
“…This requires further exploration and development of the relevant tools to formulate cases in ways that allow the use of a cultural defense when appropriate. The study of culture in forensic psychiatry can help contextualize an offender's action and experience (Dein & Bhui, 2013).…”
Section: Discussionmentioning
confidence: 99%